Depolarization Property of Cirrus Clouds Over Hanoi - Pham Minh, Tien; Nguyen Xuan, Tuan; Dinh Van, Trung; Le Duy, Manh; Bui Van, Hai (Communications in Physics, 2017)
Cirrus cloud is one of the most commonly occurring cloud types globally. The clouds are found mainly to consist of floating ice crystals, which can reflect strongly incoming radiation. Lidar measurements provide an opportunity to study the microphysics and ice compositions of cirrus clouds. We have developed a polarization lidar system to measure the depolarization characteristics of the lower atmosphere over Hanoi. From our measurements of cirrus clouds over the period from 2010 to 2012, the depolarization ratio of cirrus clouds is found to be very high ranging from 20% up to 80%, indicating large fraction of backscattering from ice crystals. We find a trend of increasing depolarization ratio with height and decreasing temperature. We also compare our lidar measurements with other results obtained by lidar technique in other regions of the world